2019
DOI: 10.1016/j.cobeha.2018.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and transgenerational inheritance of behavioral phenotypes

Abstract: Adult animal behaviors are determined by complex and dynamic changes in gene expression in different brain regions and are influenced by life experiences and environmental exposures. These stimuli affect gene expression through intricate mechanisms of regulation that largely implicate epigenetic factors, such as, DNA methylation, histone post-translational modifications, and non-coding RNAs (ncRNAs). Through these molecular pathways, some of the behavioral phenotypes associated with life experiences can be sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The impacts of prenatal stress on offspring phenotypes have been particularly well studied. Prenatal stress can alter gene expression leading to long‐term impacts on the social behaviour of offspring, helping to explain why individuals consistently vary in their sociability (Jawaid & Mansuy, 2019). Prenatal stress is typically associated with reduced sociability, as demonstrated in rats (Takahashi, Haglin & Kalin, 1992) and rhesus macaques M. mulatta (Clarke & Schneider, 1993).…”
Section: The Proximate Causes: External Influencesmentioning
confidence: 99%
“…The impacts of prenatal stress on offspring phenotypes have been particularly well studied. Prenatal stress can alter gene expression leading to long‐term impacts on the social behaviour of offspring, helping to explain why individuals consistently vary in their sociability (Jawaid & Mansuy, 2019). Prenatal stress is typically associated with reduced sociability, as demonstrated in rats (Takahashi, Haglin & Kalin, 1992) and rhesus macaques M. mulatta (Clarke & Schneider, 1993).…”
Section: The Proximate Causes: External Influencesmentioning
confidence: 99%
“…Matters are further complicated when one considers that the effects of historical or generational traumas, including the impact of widespread famine occurring in previous generations, can be highly influential on subsequent progeny via epigenetic mechanisms [75][76][77][78][79][80][81][82][83][84]. Such effects are reported to occur even when the individual has not had direct contact with the trauma itself or the traumatized relative [85][86][87][88][89]. DNA methylation, which is a measure of epigenetic change and which ostensibly mediates such effects, has been associated with a number of changes in mental illness phenotypic manifestations, including brain structure and function, that are relevant to EDs, PTSD and other trauma-related disorders [76][77][78][90][91][92][93][94][95][96][97][98][99].…”
Section: Generational Embodiment (Genetics) / Historical Trauma (Epig...mentioning
confidence: 99%
“…Despite record breeding population sizes, behavioral strategies to avoid hunting pressure during autumn and winter may be partially responsible for the observed declines in mallard and other waterfowl harvest in west Tennessee and elsewhere (Raftovich et al, 2022). Evolutionarily, these movement and resource selection behaviors, which may be connected to intense hunting pressures, could be passed down across generations (Jawaid & Mansuy, 2019; Plomin, 1990). Other studies across taxa have shown that once alternative movement and selection patterns are established, historic behaviors are challenging and costly to restore (Allred, 1950; Barker et al, 2022).…”
Section: Discussionmentioning
confidence: 99%